Safety and efficacy of a feed additive consisting of Saccharomyces cerevisiae CNCM I‐1079 for dogs and all other Canidae (Danstar Ferment AG) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of Saccharomyces cerevisiae CNCM I‐1079 as a zootechnical feed additive for dogs and all other Canidae. The additive is intended for use in feed for dogs and all other Canidae at a proposed minimum inclusion level of 1 × 109 CFU per kg of complete feed. Saccharomyces cerevisiae is considered by EFSA to be suitable for the qualified presumption of safety approach to safety assessment. Since the identity of the active agent has been clearly established and no concerns are expected from other components of the product, the additive is considered safe for the target species. Since the additive is intended to be used only in feed for dogs and other non‐food‐producing animals, an assessment of the safety for the consumer and the environment is not needed. The non‐coated form of the additive was shown to be non‐irritant to skin and eyes. No conclusion can be drawn on the eye irritation potential of the coated form of the additive due to the lack of data. The additive in both forms, should be considered a skin and respiratory sensitiser and any exposure through skin and respiratory tract is considered a risk. The Panel was not in the position to conclude on the efficacy of Saccharomyces cerevisiae CNCM I‐1079 at the proposed conditions of use.